Income Distribution, Borrowing Constraints and Redistributive Policies - Carlotta Berti Ceroni; Giorgio Bellettini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1999)
This paper proposes an explanation for why universal suffrage has not implied larger rich-to-poor transfers of wealth. The main argument is that, in the presence of borrowing constraints, if current taxation finances (at least partially) policies that redistribute future income, the poor, who are more likely to be liquidity constrained, may form a coalition with the rich and vote for low redistribution. In this context, the effects of an increase in income inequality is concentrated among the poor or the middle class. In the former case, an increase in inequality tends to decrease redistribution, whereas, in the latter case, it tends to increase redistribution.
Keywords: 330